Sahita’s Performance, Satire of the Life of Javanese Women - Yustina Devi Ardhiani (Graduate School of Institut Seni Indonesia Yogyakarta, 2016)
Sahita is a performance art group established in Surakarta-Central Java with four members of Javanese women who are in their forties to fifties. On stage performance, Sahita acts upon old women who are not pretty, but plump, attractive, energic, and humorous. Their performance is considered “uncommon” considering the fact that Sahita’s cultural background is Javanese which is dominated by youth, beauty, proportional body as the beauty of female bodily form, and gentle manner as women described on stage performance. The research questions highlights why Sahita prefers to have satire style and chooses traditional art as the basis in producing new works? The data are gained through field observation, deep interview and library study. The finding reveals that Sahita prefers the satire style to express what is hard to talk in the daily life and to express critics in humorous ways so that the critized party can also enjoy the performance. In their works, Sahita makes traditional art as its base because of its strong background in traditional art and because of its unlimited exploration. What makes Sahita unique besides its members who are all women voicing women’s anxiety, Sahita also presents traditional art with contemporary taste in their works.